Drug-drug-interactions in patients with atrial fibrillation admitted to the emergency department - Bischof, Thorsten; Nagele, Fiona; Kalkofen, Marius M.; Blechschmidt, Maximilian E. O.; Domanovits, Hans; Zeitlinger, Markus; Schoergenhofer, Christian; Cacioppo, Filippo (Frontiers in Pharmacology, 2024)
Polypharmacy is a growing concern in healthcare systems. While available data on potential drugdrug interactions (pDDI) from emergency department (ED) patients is derived from heterogenous populations, this study specifically focused on patients with atrial fibrillation (AF). We hypothesized that patients with AF have similar comorbidities, receive similar drugs, and have similar pDDIs. The overarching aim was to highlight frequent pDDIs, providing practical guidance for treating health care professionals and consequently reduce the risk of adverse drug reactions.Two hundred patients ≥18 years with AF, who received rate-or rhythm-controlling medication at the ED of the University Hospital Vienna, and who were on long-term medication before admission, were eligible. Long-term medication alone, as well as in combination with medication administered at the ED were analyzed for pDDIs using the Lexicomp® Drug interactions database.Within the long-term medication of patients', we identified 664 pDDIs. Drugs administered at the ED increased pDDIs more than 3-fold to 2085. Approximately, every fifth patient received a contraindicated drug combination (on average 0.24 per patient), while 70% received drug combinations for which therapy modifications are recommended (on average 1.59 per patient). The most frequently involved drugs included amiodarone, propofol, bisoprolol, enoxaparin, and acetylsalicylic acid. Increased risk of bleeding, QTc prolongation, and myopathy were among the most relevant potential consequences of these interactions.In conclusion, an optimization of medication would be advisable in almost every AF patient. Treating health care professionals should be cautious of drugs that increase bleeding risk, prolong QTc, or bear a risk for myopathy.